2018
DOI: 10.1159/000495921
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of microRNAs in Drug-Resistant Non-Small Cell Lung Cancer Cell Lines Using microRNA Sequencing

Abstract: Background/Aims: Drug resistance remains a main obstacle to the treatment of non- small cell lung cancer (NSCLC). The aim of this study was to identify the expression profiles of microRNAs (miRNAs) in drug-resistant NSCLC cell lines. Methods: The expression profiles of miRNAs in drug-resistant NSCLC cell lines were examined using miRNA sequencing, and the common dysregulated miRNAs in these cell lines were identified and analyzed by bioinformatics methods. Results: A total of 29 upregulated miRNAs and 36 downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…However, the inclusion of both metastasized and non-metastasized patients in the analysis must be noted as a limitation of the study regarding the calculation of PFS. Except for hsa-miR-1193, which was also shown to relate to lung cancer [86], to date, there are no studies to validate their involvement in carcinogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…However, the inclusion of both metastasized and non-metastasized patients in the analysis must be noted as a limitation of the study regarding the calculation of PFS. Except for hsa-miR-1193, which was also shown to relate to lung cancer [86], to date, there are no studies to validate their involvement in carcinogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs that show differential expression between anti-cancer drug-sensitive and anti-cancer drug-resistant NSCLC cells have been identified [164]. These miRNAs may affect autophagy and regulate the responses of various cancers to anti-EGFR treatments.…”
Section: Mirnas Regulate Response Of Cancer Cells To Anti-egfr Trementioning
confidence: 99%
“…[24][25][26][27] MiRNAs are reported to be involved in drug resistance in cancer, and could be regarded as therapeutic targets for lung cancer. 28,29 According to the results of multiple linear regression and support vector regression models in our previous study, there is a negative association between the expression levels of miR-30a-5p and phosphoinositide-3-kinase regulatory subunit 2 (PIK3R2). 19 In another study, we found that overexpression of miR-30a-5p could significantly reduce expression of PIK3R2 to further induce cell apoptosis, as well as inhibiting cell invasion and migration properties, indicating its potential in overcoming acquired resistance to EGFR-TKIs.…”
Section: Introductionmentioning
confidence: 99%